O significado da salvação na História Eclesiástica de Eusébio de Cesaréia - Corbellini, Vital (Teocomunicação, 2006)
Eusebius of Caesarea tries to underwrite in his Ecclesiastical History the salvific aspect of our Lord Jesus Christ with the collaboration of his disciples. God’s purpose, as economy, was achieved by the incarnation of the Logos. The two first books of this work show the reality of the Church: persecutions and other sufferings on account of Christ. At the end the presence of our Lord will guarantee the victory of the Church.